Arduino based monitoring system for materials used in façade rehabilitation − Experimental study with lime mortars. (June 2022) - Ferrández, Daniel; Yedra, Engerst; Atanes-Sánchez, Evangelina; Morón, Carlos
Abstract: Today's society is increasingly aware of the conservation of architectural heritage and, at the same time, is committed to the use of new technologies in construction and the use of more sustainable construction materials. This work has a double objective, on the one hand, to develop new measurement equipment based on Arduino platform for the monitoring of moisture and temperature parameters, and on the other, to determine the evolution of these properties and the physical-mechanical characteristics of lime-based mortars used in rehabilitation works. An experimental campaign has been carried out where two types of hydraulic lime mortars have been used that differ according to the aggregate either, natural or mixed recycled ceramic. The results show how it is possible to monitor in real-time the temperature and moisture parameters in the mortars from the beginning of the setting process, which is of great relevance for the control of the execution process in restoration works. Besides, it has been possible to observe how lime mortars with recycled aggregate present good technical performance for use in rehabilitation works, although without reaching the physical and mechanical properties of traditional mortars.